Analysis of the relationship between using personal protective equipment (PPE) masks on the incidence of respiratory symptoms disorders of online motorcycle taxis drivers in Malang - Jeremi Setiawan; Hanna Cakrawati; Anung Putri Illahika (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
ABSTRACT  Health problems that are often encountered due to work are respiratory disorders that cause premature death every year. Exposure to pollution is harmful to health, and chronic exposure causes lung cancer and COPD. The use of masks is an alternative in reducing exposure to pollution. This study aimed to determine the relationship between the habit of wearing masks on the incidence of respiratory symptoms disorder of online motorcycle taxi drivers in Malang. This study was an analytic observation with a cross-sectional design. Samples were determined using the comparative bivariate analytical sample formula. The data were analyzed using a univariate test and bivariate analysis with a chi-square test. This study showed a significant relationship between the habit of wearing a mask with p score = 0.015 (p<0,05), changing time with p score = 0.004 (p<0,05), and the type of mask on respiratory symptoms disorders with p score = 0.006 (p<0,05). The results obtained regarding the description of the habit of using masks, the results of the method of using masks were mainly in the good category. In conclusion, there is a significant relationship between the habit of wearing masks and the incidence of respiratory symptoms disorders among online motorcycle taxi drivers in Malang. Keywords             : Habits, masks, symptoms of respiratory disorders, online motorcycle taxisCorrespondence   : Jeremisetiawan@webmail.umm.ac.id